Trends and forecasting of infant and perinatal mortality in the Republics of Tuva, Khakassia and Mongolia - Agarkov, Nikolay M.; Fabrikantov, Oleg L.; Yemelyanov, Sergey G.; Titov, Anton A.; Alymova, Maria V.; Shorokhova, Anastasia A. (The New Research of Tuva, 2025)
The article presents the results of an analysis of the dynamics of infant and perinatal mortality, as well as the projected levels of these specific demographic indicators in two Russian republics — Tuva and Khakassia — and in the neighboring country of Mongolia. The study is based on official statistical data from these territories for the period 2019–2022. To assess the dynamics and intensity of changes, authors used a variety of indicators, including absolute growth (or decrease), growth rates, and rates of change, calculated using standard methods.A comparative analysis of the trends in infant and perinatal mortality in the two republics of the Russian Federation and in Mongolia is presented. It was found that the average level of infant mortality is statistically significantly higher in Mongolia than in the Republic of Khakassia and the Republic of Tuva. The calculated indicators of absolute change and growth rate indicate a decrease in infant mortality in the Republic of Tuva from 2019 to 2022 and an increase in the Republic of Khakassia, while changes in Mongolia were negligible.The level of perinatal mortality in the Republics of Tuva and Khakassia showed no significant differences, although in both republics there was a statistically significant increase in absolute growth and growth rate, with a more substantial increase observed in the Republic of Khakassia. In Mongolia, perinatal mortality was significantly higher.In the coming years, an increase in perinatal mortality is projected for the Republics of Tuva and Khakassia, along with a rise in infant mortality in the Republic of Khakassia and a decrease in the Republic of Tuva. In Mongolia, these indicators are expected to remain largely unchanged.
Keywords: Republic of Tuva; Republic of Khakassia; Mongolia; infant mortality; perinatal mortality; forecasting